2014
DOI: 10.1186/scrt468
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes impairs the angiogenic potential of adipose-derived stem cells by selectively depleting cellular subpopulations

Abstract: IntroductionPathophysiologic changes associated with diabetes impair new blood vessel formation and wound healing. Mesenchymal stem cells derived from adipose tissue (ASCs) have been used clinically to promote healing, although it remains unclear whether diabetes impairs their functional and therapeutic capacity.MethodsIn this study, we examined the impact of diabetes on the murine ASC niche as well as on the potential of isolated cells to promote neovascularization in vitro and in vivo. A novel single-cell an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 155 publications
(126 citation statements)
references
References 36 publications
5
120
0
1
Order By: Relevance
“…Our data suggest that use of the proper matrix components, at physiological density and configuration, promotes MSC survival and function to promote wound healing. Interestingly, diabetes is associated with diminished subpopulations of MSCs, suggesting that diabetic ulcers may be amenable to therapies that restore MSC numbers and/or function [37,38]. The stem cell niche provides a microenvironment conducive for stem cell survival and maintenance of multipotency.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that use of the proper matrix components, at physiological density and configuration, promotes MSC survival and function to promote wound healing. Interestingly, diabetes is associated with diminished subpopulations of MSCs, suggesting that diabetic ulcers may be amenable to therapies that restore MSC numbers and/or function [37,38]. The stem cell niche provides a microenvironment conducive for stem cell survival and maintenance of multipotency.…”
Section: Discussionmentioning
confidence: 99%
“…8 Stem cells and progenitor cells are dysfunctional at both a population-wide and a single-cell level in diabetes. 14 It would be expected, therefore, that correcting or treating diabetes will restore the function of these progenitors and prevent further tissue complications. However, this is not always the case.…”
Section: Diabetic Stem and Progenitor Cell Defects Are Reversible Onlmentioning
confidence: 99%
“…104 Similarly, bone marroweMSC and ASC transplants have been tested for the modulation of diabetic nephropathy and for the treatment of nonhealing diabetic wounds resulting from neuropathy and microvasculopathy. 14,105,106 This section details the various approaches of using autologous stem cells for treating diabetic complications.…”
Section: Treating Diabetic Complicationsmentioning
confidence: 99%
“…However, the diabetic status of the patients in this trial did not correlate with response, 68 which is surprising given recent studies showing diabetes impairs the ability of ASCs to promote neovascularization (via subpopulation depletion). 69 Not all studies have shown that chronic systemic disease impairs stem cell functionality. Smadja et al 70 noted that BM-MSCs harvested from CLI patients and healthy controls demonstrate similar proangiogenic effects when transplanted into CLI-induced mice.…”
Section: Stem Cells Harvested From Patients With Chronic Diseasementioning
confidence: 99%